2020
DOI: 10.18821/0869-2084-2020-65-2-95-99
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Markers of Hepatitis B and D Virus Infection in Biological Media and Dried Blood Spots

Abstract: The aim of this study was to assess the rates of detection of the major markers of infection with hepatitis B and Delta (D) viruses in serum, saliva and dry blood dots (DBS) as a possible option for serological studies among the population of the endemic region in conditions of limited laboratory resources. For this purpose, paired samples of blood serum and DBS, blood serum and saliva from patients with chronic hepatitis B with Delta agent living in the Republic of Tyva, which is endemic for this disease. HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Currently, there is insufficient data on whether HDV particles could be carried by saliva, similar to HBV. Only one study, performed by Isaeva et al, focused on this topic but found no detection of HDV antibodies in saliva samples originating from patients with HBV and HDV infection [ 48 ]. Despite the fact that the saliva samples were positive for HBV antigens and antibodies, this was not the case for HDV, suggesting a lower concentration of these elements in the saliva than for HBV [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is insufficient data on whether HDV particles could be carried by saliva, similar to HBV. Only one study, performed by Isaeva et al, focused on this topic but found no detection of HDV antibodies in saliva samples originating from patients with HBV and HDV infection [ 48 ]. Despite the fact that the saliva samples were positive for HBV antigens and antibodies, this was not the case for HDV, suggesting a lower concentration of these elements in the saliva than for HBV [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study, performed by Isaeva et al, focused on this topic but found no detection of HDV antibodies in saliva samples originating from patients with HBV and HDV infection [ 48 ]. Despite the fact that the saliva samples were positive for HBV antigens and antibodies, this was not the case for HDV, suggesting a lower concentration of these elements in the saliva than for HBV [ 48 ]. Nevertheless, the matter should be addressed by complementary research in order to increase its scientific understanding.…”
Section: Resultsmentioning
confidence: 99%